Optimization of the multi-carburant dose as an energy source for the application of the HCCI engine. (1st October 2019) - Bastawissi, Hagar Alm ElDin; Elkelawy, Medhat; Panchal, Hitesh; Kumar Sadasivuni, Kishor
Highlights: The improvement of the CNG HCCI engine relies on the aid of double fuel additives. The engine knocking limits relies on the ratio of the each fuel additives. The 10% of hydrogen dose in the charged mixture improves the engine performance. DME fuel rang in the mixture vary from the 15 and 70% to prevent engine misfire. The proposed additives doses obtained the optimized CNG HCCI engine operation. Abstract: The issue of utilizing multi-fuels for enhancing the burning process in the "Homogeneous charge compression ignition" HCCI engine cylinder has been developing significantly during the last decades. This technique has established to overcome the difficulties of the engine ignition and knock-like combustion control when distinguished with utilizing a single fuel during the engine management system. Furthermore, the developing concern towards the cleaner environment and the battle against wonderful weather by using the renewable fuel types are urgently required. In this research, the theoretical and experimental study will achieve the possibility of preparing a charged mixture, which consists of the air and three different kinds of alternative fuels. The prepared mixture was introducing into a mixing chamber near the intake manifold of the HCCI engine working at varying load conditions. Those fuels were the natural gas, hydrogen, and "Dimethyl ether" as a biodiesel fuel. The mixture has been utilizing to enhance the HCCI engine performance. However, the non-petroleum based alternative fuel such as "Dimethyl ether" DME has been used as an additive to the mixes of the natural gas or natural gas/hydrogen blends. Current methodology has been acquainting to make the chance of the engine ignition control is accessible, alongside its advantages to keeping away from the engine knocking or misfire operation. The ideal dose of each type of the tri-fuels composition with different percentages of each fuel used has been optimizing. Natural gas fuel is the primary fuel of the engine, and the other two types of fuel have used as additives for renewable fuels. The obtained results showed that there are certain proportions for each kind of the employed fuel in which the possibility of the engine operation without the occurrence of the knock-like combustion or the apparent of misfire operation have been achieving.